The Influence of Teacher Trainees’ Attitude towards Objectives of Home Science Education in Kenya - Sempele , Catherine; Natade , Jacob; Otunga , Ruth (African Journal of Education,Science and Technology (AJEST), 2018)
A major challenge affecting the teaching of Home Science is related to the attitudes both students and society have towards the subject. Attitudes are an internal state that influences the personal actions of an individual. Home Science Education has been stereotyped as a subject for girls and women only and as a subject for the academically weak students. The society perceives it as a subject that does not require one to go to school in order to study it. Attitudes form an integral component of the context of curriculum implementation which influences the achievement of both educational and instructional objectives to a great extent. This study sought to establish how teacher trainees’ attitude towards Home Science Education affects the extent to which course objectives are being achieved. Three hundred and eighteen teacher trainees (318) and thirty (30) primary school teachers took part in this study. Research information was collected by use of self administered questionnaires. Results obtained showed that generally, teacher trainees have a positive attitude towards Home Science Education. Regression analysis results (β=0.069, p=0.002) showed a significant relationship between teacher trainees’ attitude towards the subject and achievement of course objectives. The study concluded that teacher trainees’ attitude towards Home Science Education significantly contributes towards achievement of course objectives, thus recommends that there is need to sensitize the general society including primary school pupils, parents, high school students and all teacher trainees on the benefits of Home Science Education. This should be done by the Ministry of Education, Public health practitioners, Primary Teacher Training Colleges and all Home Science teachers in the country. This will help improve societal perceptions towards the subject given that it is bound to improve individuals, families and societal standards of living